A New BFGS Algorithm Using the Decomposition Matrix of the Correction Matrix to Obtain the Search Directions - Li Liu (Journal of Control Science and Engineering)
We present an improved method for determining the search direction in the BFGS algorithm. Our approach uses the equal inner product decomposition method for positive-definite matrices. The decomposition of an approximated Hessian matrix expresses a correction formula that is independent from the exact line search. This decomposed matrix is used to compute the search direction in a new BFGS algorithm.